The efficacy of cooling with phase change material for the treatment of exercise-induced muscle damage: pilot study - Kwiecien, S. Y.; McHugh, M. P.; Howatson, G. (Journal of Sports Sciences, 2018)
Post-exercise cryotherapy treatments are typically short duration interventions. This study examined the efficacy of prolonged cooling using phase change material (PCM) on strength loss and pain after eccentric exercise. Eight adults performed 120 bilateral eccentric quadriceps contractions (90% MVC). Immediately afterwards, frozen PCM packs (15°C) were placed over the quadriceps, with room temperature PCM packs on the contralateral quadriceps. Skin temperature was recorded continually (6 h PCM application). Isometric quadriceps strength and soreness were assessed before, 24, 48, 72 and 96 h post-exercise. The protocol was repeated 5 months later, with room temperature PCM applied to both legs. There were three treatments: legs treated with 15°C PCM packs (direct cooling), legs treated with room temperature PCM packs contralateral to the 15°C PCM packs (systemic cooling), and legs tested 5 months later both treated with room temperature PCM packs (control). Skin temperature was 9°C-10°C lower with direct cooling versus systemic cooling and control (P < 0.01). Strength loss and soreness were less (P < 0.05) with direct cooling versus systemic cooling and control (strength 101%, 94%, 93%, respectively; pain 1.0, 2.3, 2.7, respectively). Six hours of PCM cooling was well tolerated and reduced strength loss and pain after damaging exercise.